Aerobic Photooxidative Cleavage of Vicinal Diols to Carboxylic Acids Using 2-Chloroanthraquinone - Matsusaki, Yoko; Yamaguchi, Tomoaki; Tada, Norihiro; Miura, Tsuyoshi; Itoh, Akichika (Synlett, 2012)
We developed the aerobic photooxidative cleavage of vicinal diols to carboxylic acids using 2-chloroanthraquinone in the presence of photoirradiation with a high-pressure mercury lamp. This is the first metal-free reaction using molecular oxygen as the terminal oxidant.
Keywords: photooxidation; aerobic; anthraquinone; vicinal diol; carboxylic acid